Leisure lifestyles of childless couples vs. Full nest - Gallego Martelo, Sandra María; Ceballos, Lina María; Mejia-Gil, Maria Claudia (Estudios de Administración, 2020)
Despite multiple studies related to lifestyles and family life cycles, few academics have concentrated on leisure topics in emerging countries, such as Colombia. This qualitative study involved 16 in-depth interviews and a total of 32 participants as it explored lifestyles in terms of leisure among couples according to their family life cycle, specifically couples starting a life together (couples without children) and those who are already in the stage of raising young children (full nest). Literature indicates that lifestyles and leisure are directly related to the family’s economic situation; therefore, this study focuses on higher-income participants, represented by individuals from the upper-middle and upper strata (5 and 6) in the city of Medellín, Colombia (South America). In terms of leisure, the findings reveal similar lifestyles in both types of couples; however, the availability of time, frequency and the types of products or services in which these couples invest their time and money evidence certain differences, especially when there are children. This study could be useful for marketing managers whose target market relates to homes with young families.